2016
DOI: 10.1111/jade.12046
|View full text |Cite
|
Sign up to set email alerts
|

Looking for a Possible Framework to Teach Contemporary Art in Primary School

Abstract: Traditionally, the learning of arts in the Estonian primary school has meant completion of practical assignments given by the teacher. The new national curriculum for basic school adopted in 2010 sets out new requirements for art education where the emphasis, in addition to practical assignments, is on discussion and understanding of art. The teacher must introduce pupils to both art history and contemporary art. As a result, primary teachers would likely serve their pupils more effectively if they reconsidere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…In this study the researchers conducted action research by applying drawing learning through media appreciation of contemporary art. The results of the study concluded that learning through appreciation of contemporary art can produce more student images variative [1]. One of the characteristics of a creative picture is the object that is drawn varied.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study the researchers conducted action research by applying drawing learning through media appreciation of contemporary art. The results of the study concluded that learning through appreciation of contemporary art can produce more student images variative [1]. One of the characteristics of a creative picture is the object that is drawn varied.…”
Section: Introductionmentioning
confidence: 93%
“…The influence of cognitive development theories and humanistic approaches is so great on the innovation of teaching and learning processes over the past few decades [1]. Another form of learning in drawing is called Picture and Picture learning [3].…”
Section: A Analogy Learning Process and Drawing Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of previous research on drawing learning, it can be concluded that the average image results are monotonous [1][2][3]. The same thing happened in other countries, namely in Estonia [4] which resulted in the study that most of the monotonous image results.…”
Section: Introductionmentioning
confidence: 93%
“…Learning is the process of interaction between students, teachers, and the environment to achieve certain abilities [13,14]. In learning requires a learning approach.…”
Section: A Learning To Draw Illustrationsmentioning
confidence: 99%